THE USE OF BAHASA INDONESIA IN LEARNING “ENGLISH SPECIAL PURPOSE” : A STUDY AT MATHEMATIC DEPARTMENT IN IKIP BUDI UTOMO MALANG - Indrawati Pusparini (UIBU, 2018)
Acquiring English, for several students, can be very tough especially for student that have already used Indonesia language in daily learning. In this extent, The student are seemed in the boundary of learning not acquiring English. In learning English, the student in Ikip Budi Utomo tend to use Bahasa Indonesia, especially who study English Special Purpose in Ikip Budi Utomo. Making use of Bahasa Indonesia might help them a lot in learning English. The researcher, then, was eager to figure out in what way the students who study English Special Purpose in Mathematic department were assisted by Bahasa Indonesia in learning English Special Purpose. The research method used in this study is a qualitative research design.